Electrode Engineering in Halide Perovskite Electronics: Plenty of Room at the Interfaces. Issue 18 (11th March 2022) - Lin, Chun‐Ho; Hu, Long; Guan, Xinwei; Kim, Jiyun; Huang, Chien‐Yu; Huang, Jing‐Kai; Singh, Simrjit; Wu, Tom
Abstract: Contact engineering is a prerequisite for achieving desirable functionality and performance of semiconductor electronics, which is particularly critical for organic–inorganic hybrid halide perovskites due to their ionic nature and highly reactive interfaces. Although the interfaces between perovskites and charge‐transporting layers have attracted lots of attention due to the photovoltaic and light‐emitting diode applications, achieving reliable perovskite/electrode contacts for electronic devices, such as transistors and memories, remains as a bottleneck. Herein, a critical review on the elusive nature of perovskite/electrode interfaces with a focus on the interfacial electrochemistry effects is presented. The basic guidelines of electrode selection are given for establishing non‐polarized interfaces and optimal energy level alignment for perovskite materials. Furthermore, state‐of‐the‐art strategies on interface‐related electrode engineering are reviewed and discussed, which aim at achieving ohmic transport and eliminating hysteresis in perovskite devices. The role and multiple functionalities of self‐assembled monolayers that offer a unique approach toward improving perovskite/electrode contacts are also discussed. The insights on electrode engineering pave the way to advancing stable and reliable perovskite devices in diverse electronic applications. Abstract : Rational selection of electrodes plays a critical role in perovskite‐based electronics due to the high reactivity of halide perovskite materials. A comprehensive review of perovskite/electrode interfaces, as well as, state‐of‐the‐art contact engineering, which assists the development of perovskite‐based devices with inhibited interfacial reactions, ohmic carrier transport, and non‐hysteric electronic characteristics, is presented.